Experimental characterisation of fatigue damage in single Z-pins. (December 2016) - Warzok, F.; Allegri, G.; Gude, M.; Hallett, S.R.
Abstract: Z-pins have been shown to significantly improve delamination resistance and impact strength of carbon fibre reinforced (CFRP) composites. In this paper, an experimental investigation of the influence of different fatigue parameters (mean opening/sliding displacement, amplitude, frequency, number of cycles) on the through-thickness reinforcement (TTR) is presented. For mode I, it is shown that the degradation on pin behaviour during fatigue is mostly affected by the applied displacement amplitude. The degradation is primarily caused by surface wear. Due to the brittleness of the Z-pins, mode II fatigue does not have a significant effect for very small sliding displacements. Exceeding a critical displacement causes the pin to rupture within the very first cycles.